n is an integer greater than 1. Prove algebraically that n^2 – 2 – (n – 2)^2 is always an even number.

1) Expand the brackets: (n-2)2 = (n-2)(n-2) = n2 - 2n - 2n +4 = n2 - 4n + 42) Substitute this into the original expression: n2- 2 - (n2 - 4n +4) = n2 - 2 - n2 + 4n - 4 = 4n - 6 3) Reduce this: 4n - 6 = 2(2n - 3)4) Conclusion: This is always an even number as for all values of n the expression is a multiple of 2

Answered by James M. Maths tutor

4521 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Factorise x^2-x-12


The probability of obtaining heads on a biased coin is 0.4. The coin is tossed 600 times. Write down the mean number of heads and the standard deviation of the number of heads.


Solve for x: 2x+3+((4x-1)/2)=10


s^2 - 2s - 24 = 0


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences